Syphilis seroprevalence estimates of Santa Catarina blood donors in 2010 - Baião,Aysla Marcelino (2014)
Introduction Knowledge of blood donor characteristics is essential to better guide clinical and serological screening for hemotherapy. The objective of this study was to determine the syphilis seroprevalence and the associated factors of blood donors in the State of Santa Catarina, Brazil. Methods This population-based study from the State of Santa Catarina used information obtained from blood donation records. We analyzed 83,396 blood donor records generated from donors who were considered eligible to donate between January and August 2010. The aim of the study was to estimate the syphilis seroprevalence and its relationship with educational level, age, gender, geographical region and having donated blood in the past 12 months. We used descriptive analyses and a Poisson regression to calculate the prevalence ratios for the variables of interest. Results We found a 0.14% overall seroprevalence and significant differences among the following: first-time blood donors (0.19%) versus repeat donors (0.03% to 0.08%); low educational levels (0.30%) versus medium and high educational levels (0.08% to 0.19%); and donors who did not report their residence (0.88%) or age (6.94%) versus those who did. Increased syphilis seroprevalence was also significantly associated with increased age. Conclusion High syphilis seroprevalence was associated with lower educational level, age, first-time donation and the failure to provide age or residence information.